2018
DOI: 10.1016/j.rmcr.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Tension hydropneumothorax as the initial presentation of Boerhaave syndrome

Abstract: Boerhaave syndrome, a rare yet frequently fatal diagnosis, is characterized by the spontaneous transmural rupture of the esophagus. The classic presentation of Boerhaave syndrome is characterized by Mackler's triad, consisting of chest pain, vomiting, and subcutaneous emphysema. However, Boerhaave syndrome rarely presents with all the features of Mackler's triad; instead, the common presentation of Boerhaave syndrome includes chest or epigastric pain, severe retching and vomiting, dyspnea, and shock. These sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…In summary, we present an unusual case of esophageal perforation in a critically ill patient and highlight the importance of including acute esophageal pathology in the differential for a decompensating host in the ICU. Although tension hydropneumothorax has been previously reported as a rare complication of esophageal perforation due to Boerhaave syndrome, these entities have not been previously described in relation to septic shock [ 10 ]. Our review of the literature suggests that intervention within the first 24 hours leads to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we present an unusual case of esophageal perforation in a critically ill patient and highlight the importance of including acute esophageal pathology in the differential for a decompensating host in the ICU. Although tension hydropneumothorax has been previously reported as a rare complication of esophageal perforation due to Boerhaave syndrome, these entities have not been previously described in relation to septic shock [ 10 ]. Our review of the literature suggests that intervention within the first 24 hours leads to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst published case worldwide demonstrating esophageal rupture located in the right wall after taking magnesium sulfate. A study revealed that the incidence of spontaneous oesophageal perforation was 3.1/1,000,000 per year, which is an extremely rare entity [6], and the common presentations of BS, including chest or epigastric pain, vomiting, dyspnea and shock, are vulnerable to misdiagnosis as other entities, such as entities cardiogenic in origin, gastrointestinal perforation, acute pancreatitis and abdominal aortic aneurysms [7]. Due to the low incidence rate and high misdiagnosis rate of BS, the diagnosis and therapy of BS are often delayed, resulting in a high mortality and signi cant complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, images including plain chest roentgenograms, oesophagograms, and CT scans also contribute to diagnosing BS [8]. Previous studies have shown that the oesophagogram is a feasible and effective examination for diagnosing oesophageal perforation [5]; however, due to the high false-negative rate of the oesophagogram (15-25%) and tenuous nature of oesophageal rupture, chest CT is considered a more appropriate modality [5,7]. The typical ndings of chest radiography and CT are subcutaneous emphysema, pneumomediastinum, pleural effusion, pneumothorax, and so on [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is an uncommon condition frequently associated with severe retching and vomiting often associated with alcoholism ; it has an estimated incidence of 3.1 per 1,000,000 per year [5]. It is usually recognized immediately it occurs, presenting with the typical Mackler's triad of chest pain, vomiting and subcutaneous emphysema [6][7][8][9]. However, in few cases, this triad may not be complete, or may be missed and thus present late with complications [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%